2008
DOI: 10.1007/s11154-007-9069-6
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease in children: Impact on bone health

Abstract: Celiac disease is a chronic enteropathy caused by permanent intolerance to gluten and similar proteins found in wheat, barley and rye. The intestinal mucosa of susceptible individuals is crossed by undigested gluten, which leads to a marked inflammatory response. The clinical features may vary from overt intestinal symptoms to silent disease. Bone health has been found to be markedly affected in children and adolescents with untreated celiac disease, regardless of clinical presentation. Bone mass measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 63 publications
0
27
0
4
Order By: Relevance
“…A chronic malabsorption of nutrients affects bone formation (vitamins D and K, and calcium), whereas chronic intestinal inflammation (increased production of cytokines and autoimmune alterations) and trace element and magnesium deficiencies may be factors involved in low BMD in patients with CD (4,17). Several adult studies have reported that vitamin K plays an important role in optimizing bone health (18)(19)(20), and an increased fracture risk has been reported in individuals with low vitamin K intake (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A chronic malabsorption of nutrients affects bone formation (vitamins D and K, and calcium), whereas chronic intestinal inflammation (increased production of cytokines and autoimmune alterations) and trace element and magnesium deficiencies may be factors involved in low BMD in patients with CD (4,17). Several adult studies have reported that vitamin K plays an important role in optimizing bone health (18)(19)(20), and an increased fracture risk has been reported in individuals with low vitamin K intake (21).…”
Section: Discussionmentioning
confidence: 99%
“…Micronutrient malabsorption, inflammatory cytokines, and autoimmunity may impact bone metabolism in CD. Impaired absorption of necessary nutrients for bone mineralization such as calcium and vitamins D and K may represent the principal cause of low BMD (4). Previous studies of adults have proposed that vitamin K exhibits a beneficial role in bone mineral metabolism by acting as a cofactor in the post-translational carboxylation of several bone proteins (5).…”
Section: Introductionmentioning
confidence: 99%
“…However, the diagnostic criteria of the European Society of Paediatric Gastroenterology and Nutrition 14 were followed, and these criteria are often used. 7 Therefore, we believe that all of the patients included in the study had celiac disease. Secondly, the cross-sectional design may have led to difficulty in understanding the contributions of late treatment, good adherence to gluten-free diet and duration of treatment towards bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Several studies have demonstrated that, independent of the clinical presentation, patients with untreated celiac disease present low bone mineral density (BMD). [1][2][3]5,7,8 Osteopenia is a common public health problem in adults, but can be diagnosed and prevented in childhood. Considering that most of the bone mass is acquired during the first two decades of life, early diagnosis of celiac disease and adherence to a gluten-free diet are of fundamental importance for ensuring adequate bone metabolism in such cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation